2014
DOI: 10.1055/s-0034-1383356
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Anticancer Compounds Targeting Apoptosis and Autophagy from Chinese Native Garcinia Species

Abstract: Natural compounds from medicinal plants are important resources for drug development. Active compounds targeting apoptosis and autophagy are candidates for anti-cancer drugs. In this study, we collected Garcinia species from China and extracted them into water or ethanol fractions. Then, we performed a functional screen in search of novel apoptosis and autophagy regulators. We first characterized the anti-proliferation activity of the crude extracts on multiple cell lines. HeLa cells expressing GFP-LC3 were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 43 publications
(48 reference statements)
3
38
0
Order By: Relevance
“…The rapid development of genome sequencing technology, nanoscience, and information science will help us further explore the mechanism of TCM on multiple targets, balance adjustment, and palliative effects. For example, we apply high content analysis technology to screen anti‐cancer TCM and find the basis of materials in more effective ways . The Cancer Genome Atlas will be used in research for the detection of a connection between TCM symptom patterns and genomes .…”
Section: Future Direction Of Tcm In Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid development of genome sequencing technology, nanoscience, and information science will help us further explore the mechanism of TCM on multiple targets, balance adjustment, and palliative effects. For example, we apply high content analysis technology to screen anti‐cancer TCM and find the basis of materials in more effective ways . The Cancer Genome Atlas will be used in research for the detection of a connection between TCM symptom patterns and genomes .…”
Section: Future Direction Of Tcm In Oncologymentioning
confidence: 99%
“…For example, we apply high content analysis technology to screen anti-cancer TCM and find the basis of materials in more effective ways. 65,66 The Cancer Genome Atlas will be used in research for the detection of a connection between TCM symptom patterns and genomes. 67,68 It can also help identify multiple target effects caused by TCM intervention, in order to predict effects and guide a timely adjustment of treatment.…”
Section: Future Direction Of Tcm In Oncology Basic Researchmentioning
confidence: 99%
“…The cardiotonic steroid UNBS1450 0 from Calotropis procera was shown to autophagy-related cell death, by repressing NF-κB activation, as well as by downregulating c-MYC in cancer cells [231]. Oblongifolin C (OC), a natural small molecule compound extracted from Garcinia yunnanensis Hu , is a potent autophagic flux inhibitor, as described elsewhere [232-234]. Exposure to OC results in an increased number of autophagosomes and impaired degradation of SQSTM1/p62, as described in [233].…”
Section: Anticancer Natural Compounds and Autophagymentioning
confidence: 99%
“…In recent studies, we have shown that Neobractatin (NBT), a natural compound isolated from Garcinia bracteata by C. Y. Wu ex Y. H. Li, possesses anti-tumor activities, such as inducing cell apoptosis and inhibiting autophagic flux 13 . In this study, we also found that NBT exhibited potent anti-metastatic activity against BC and LC both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%